THE IMPORTANCE OF POVERTY REDUCTION AND POPULATION WELFARE MANAGEMENT (IN THE CASE OF BUKHARA REGION) (American Journal of Technology and Applied Sciences, 2025)
This article explores the crucial significance of poverty reduction and welfare management in the context of the Bukhara region of Uzbekistan — one of the country’s historically rich yet socioeconomically diverse territories. The study analyzes the underlying causes of poverty, examines the multidimensional nature of deprivation, and highlights the strategies and institutional mechanisms necessary to improve population welfare. Special attention is given to the government’s socio-economic reforms, employment programs, social protection systems, and the role of entrepreneurship in enhancing living standards. The paper emphasizes that sustainable poverty reduction is not limited to increasing income but involves structural transformation in education, health care, gender equality, and inclusive economic growth.